Distribution modeling of the Lamproptera species (Papilionidae: Leptocircini) in Borneo - Nur Azizuhamizah Idris,; Nuha Loling Othman,; Fatimah Abang, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Conservation planning and ecological research aimed to understand patterns of biological diversity have focused on determining threatened and rare species. Species distribution modelling had been increasingly used to understand the rare and endangered species distribution and their relationship with environmental factors. The aim of this study was to predict the potential distribution of Lamproptera butterflies across Borneo, and determine the conservation status and potential threats to their survival. Subsequent to this, species occurrence data obtained from voucher specimens of Lamproptera butterflies deposited in Universiti Malaysia Sarawak Insects Reference Collection (UIRC), Research Development and Innovation Division (RDID) of the Sarawak Forest Department, and Centre of Insects Systematics (CIS), Universiti Kebangsaan Malaysia, an extensive literature reviews and field sampling were documented. The occurrence data were later analyzed using Maxent software to obtain the potential distribution of the Lamproptera species. Majority of the high suitability area for the Lamproptera butterflies lie in the northwest part of Borneo. Environmental variables that affects the species distributions are temperature of annual range (Bio7), precipitation of driest month (Bio14), temperature seasonality (Bio4) and precipitation of wettest quarter (Bio16). Increasing knowledge on the status and distribution range regarding Lamproptera species will provided more understanding on their population dynamics and increase the effectiveness of their conservation planning.